Ensuring energy security of Armenia in a multipolar world: New tendencies and opportunities - Artur Avetisyan (OrdnungsPolitisches Portal (OPO), 2026)
Energy-sector challenges have shaped international relations since early history, making energy a key component of geopolitics. Understanding current global and regional energy and economic trends is therefore essential. Armenia, like many European Union countries, faces significant challenges in ensuring energy and economic security. Given its geographic position and self-sufficiency in electricity generation, alongside its growing export potential, Armenia can play an important role in regional energy security and stability. The country also has strong potential in renewable energy and is a regional leader in new renewables, though this potential has not yet been fully realized. Unsettled relations with Turkey and Azerbaijan, as well as infrastructure constraints with Georgia and Iran, limit Armenia's opportunities. Nevertheless, improving ties with European and Asian partners enhance Armenia's strategic role along the North-South axis. This article examines new development trends, reassesses challenges and opportunities, and evaluates Armenia's potential to act as a regional bridge for energy and economic cooperation.
Keywords: 330; Energy security; sustainability; mutually beneficial cooperation; South Caucasus; critical infrastructures; the North-South International Project; the Black Sea Electricity Cable project